ANALISIS KINERJA KEUANGAN PADA INDUSTRI KERAJINAN “ANI-ANI JEWELLARY AND CRAFT” DIDESA PANDOWOHARJO KECAMATAN SLEMAN KABUPATEN SLEMAN - Sri Ayuda; Ni Made Suyastiri Yan Permai; Budiarto Budiarto (Jurnal Dinamika Sosial Ekonomi, 2015)
The  purpose  of  this  study  are:  (1)  to  analyze  the  condition  of  the  financial performance  conducted  by industry ani - ani jewelery and craft. (2) to analyze the trend  of the industry’s  volume  sales  on ani  - ani jewellery  and  craft.  The  basic method  used  in  this  research  is  descriptive  method.  Method  of  determining  the location  of the research  is purposive.  The method  of analysis  using  profitability ratio,  to determine  the trend  in volume  sales  using  three  types  of trend  methods (Linier  Trend  method,  Quadratic  Trend  method,  and  Trend  Exponential  Method) then  the  best  results  was  selected.  The  results  showed  that  the  condition  of the industry's  financial  performance  on ani-ani  craft jewellery  and craft was in good condition. The trend in volume sales for each product on ani-ani jewellery industry and craft did not show any improvement. Keywords:Financial Performance,  Profitability  and Sales Volume Trends